Efecto del extracto hidroetanólico de semillas de Coffea arabica L. sobre la hiperplasia prostática inducida en Mus musculus var. swiss orquiectomizados - Collantes Llacza, Adela Marlene (2017)
The aim was to determine the effect of the hydroethanolic extract of Coffea arabica L. seeds on prostatic hyperplasia induced in Mus musculus var. swiss The seeds of Coffea arabica L. were purchased in Jaén, Cajamarca, obtaining the 10% hydroethanolic extract. We worked with 30 male mice, from the National Institute of Health (INS), with an average weight of 28.4 g, being distributed in 5 groups; a white group, a pathological, a referential, problem 1 and problem 2. Being acclimatized for two weeks, after which they were orchiectomized except for the white group, leaving them in recovery for fifteen days, to administer testosterone enanthate at doses of 14 mg / kg subcutaneously, repeating at 7 and 40 days. The administrations were orally, carboxymethylcellulose 10 mL / kg for the white and pathological groups, finasteride at doses of 10 mg / kg to the reference group and hydroethanolic extract of Coffea arabica L. seeds to group problem 1 and problem 2 at doses of 60 and 200 mg / kg, respectively. At the end of the study, the prostates were extracted, measuring the prostatic index, percentage of recovery and percent inhibition, in addition to histopathological examination and plasma levels of uric acid and prostate-specific antigen (PSA). Both the hydroethanolic extract of Coffea arabica L. 60 mg / kg and finasteride 10 mg / kg, reduced the prostatic index (p <0.05), while the 200 mg / kg dose of the hydroethanolic extract increased it (p <0 , 05). In terms of uric acid and PSA, both doses of Coffea arabica L. extract reduced (p <0.05) the levels. It is concluded that the hydroethanolic extract of Coffea arabica L. at low doses prevents prostatic growth, in addition both doses reduce uric acid and PSA.